Identification of phosphorylation sites in Hansenula polymorpha Pex14p by mass spectrometry. Issue 1 (12th November 2012) - Tanaka, Katsuhiro; Soeda, Maiko; Hashimoto, Yoichiro; Takenaka, Shigeo; Komori, Masayuki
Abstract : Pex14p is a peroxisomal membrane protein that is involved in both peroxisome biogenesis and selective peroxisome degradation. Previously, we showed that Hansenula polymorpha Pex14p was phosphorylated in vivo . In this study, we identified its phosphorylation site by mass spectrometry. Recombinant His‐tagged Pex14p (H6‐Pex14p) was overexpressed and purified from the yeast. The protein band corresponding to H6‐Pex14p was in‐gel digested with trypsin and subjected to LC/MS. As a result of LC/MS, Thr 248 and Ser 258 were identified as the phosphorylated sites. To confirm the phosphorylation sites and explore its functions, we made Ala mutants of the candidate amino acids. In the western blot analysis with anti‐Pex14p, S258A mutant gave doublet bands while wild type (WT) and T248A mutants gave triplet bands. Moreover, the double mutant (T248A/S258A) gave a single band. WT and all mutant Pex14p labeled with [ 32 P] orthophosphate were immunoprecipitated and analyzed by autoradiography. The phosphorylation of Pex14p was suppressed in S258A mutant, but enhanced in T248A mutant compared to WT. Moreover, the phosphorylated Pex14p was not detected in the T248A/S258A double mutant. All mutants were able to grow on methanol and their matrix proteins (alcohol oxidase and amine oxidase) were mostly localized in peroxisomes. Furthermore all mutants showed selective degradation of peroxisome like WT during the glucose‐induced macropexophagy.